2020
DOI: 10.3390/en14010002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigation on the Displacement Characteristics of CH4 by CO2, N2 and Their Mixture in a Composite Shale Model

Abstract: The rapid growth in energy consumption and environmental pollution have greatly stimulated the exploration and utilization of shale gas. The injection of gases such as CO2, N2, and their mixture is currently regarded as one of the most effective ways to enhance gas recovery from shale reservoirs. In this study, molecular simulations were conducted on a kaolinite–kerogen IID composite shale matrix to explore the displacement characteristics of CH4 using different injection gases, including CO2, N2, and their mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For example, with increasing temperature from 313.15 to 343.15 K, the displacement efficiency of CH 4 decreases from 62.12 to 59.09%. This demonstrates that a reasonable temperature (temperature of 313.15–323.15 K) accelerates the diffusion rate of CH 4 , which is conducive to enhancing the efficiency of CH 4 recovery by injecting CO 2 . …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, with increasing temperature from 313.15 to 343.15 K, the displacement efficiency of CH 4 decreases from 62.12 to 59.09%. This demonstrates that a reasonable temperature (temperature of 313.15–323.15 K) accelerates the diffusion rate of CH 4 , which is conducive to enhancing the efficiency of CH 4 recovery by injecting CO 2 . …”
Section: Discussionmentioning
confidence: 85%
“…The average diffusion rate of the CH 4 molecule is reduced from 4.4 × 10 –8 to 1.605 × 10 –8 m 2 /s, decreasing by about 1.7 times. Since the amount of CO 2 injected into the pores increases, the intermolecular van der Waals forces, viscosity, and volume expansion become stronger, which hinder the diffusion rate of CO 2 for displacing CH 4 . , In addition, there is a limited specific surface area in micropores. Increasing the injection amount of CO 2 increases the probability of intermolecular collisions and limits the average diffusion rate for intermolecular collisions .…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al constructed a composite shale model containing quartz and CNTs regions, in which CNTs and quartz were hydrophobic and hydrophilic, respectively . Gong et al built a composite shale model consisting of two kaolinite layers and two kerogen II-D layers to study the displacement characteristics of CH 4 by CO 2 , as shown in Figure . It was found that the increase of formation temperature and pore size could improve the displacement efficiency of CH 4 .…”
Section: Molecular Models Of Shalementioning
confidence: 99%
“…Shale gas in overmature shale is stored mainly as free gas and adsorbed gas, and the proportion of adsorbed gas can reach 20-85% [27][28][29]. High-pressure adsorption experiments are considered a common method to evaluate the adsorption capacity of shale and have been widely applied by many scholars [30][31][32][33]. At present, the previous studies mainly focused on the lower Paleozoic marine shales in the Upper Yangtze region.…”
Section: Introductionmentioning
confidence: 99%